Carboxylic acid ligand substituent impacts hydrosilylation activity of platinum single atom catalysts on ceria. Issue 24 (8th November 2022) - Maciulis, Nicholas A.; Wasim, Eman; Rezvani, Fereshteh; Pink, Maren; Sterbinsky, George E.; Caulton, Kenneth G.; Tait, Steven L.
Abstract : Carboxylic acid substitution in 1, 10-phenanthroline-5, 6-dione ligands bind to surface hydroxy groups and result in higher ligand loading for metal–ligand single-atom Pt catalysts on CeO2, thereby allowing excellent hydrosilylation catalysis. Abstract : Current industrially employed hydrosilylation catalysts rely on homogeneous platinum catalysts which are not recovered after the reaction. To eliminate this issue, our group has been working to optimize recyclability of heterogeneous platinum single atom catalysts (SACs) on ceria via 1, 10-phenanthroline-5, 6-dione ligands (PDO), which incorporates mono (PDO-C) and dicarboxylic acid (PDO-C2) groups in the 2- and 9-position of PDO ligand to increase metal–surface interaction. DRIFTS results confirm carboxylic acid coordination to the terminal hydroxy groups of the ceria surface. New catalyst synthesis conditions wherein PDO was combined with the metal prior to exposure to the surface allow control of Pt oxidation state on the surface. The highest metal loading was observed for PDO and PDO-C, correlating with improved catalytic recyclability compared to the PDO-C2 ligand. It is proposed that the location of the carboxylic acid groups and the steric effects can explain the lower activity and metal loading for PDO-C2 ligands. Post-reaction XPS and DRIFTS spectra show the appearance of new Si and O species on the catalyst during the hydrosilylation reaction, indicating the silane reagent is depositing on the surface. The silane coverage and leaching of catalyst from the surface is the cause for the reduced catalytic activity.